LDLCHOLESTEROLEXAMINATION (LDL-C) USINGHOMOGENEOUS ASSAY - DwiAmbara Putra, Made (E-Jurnal Medika Udayana; vol 2 no 7 (2013):e-jurnal medika udayana, 2013)
Homogeneous method describe as a method that does not require separation of free and bound label . This method has the ability tofully automate the determination of LDL - C directly small sample volume sand short examination time . In addition this method use automated pipette and control of time and temperature more accurate . There are 5 methods i.e. Solubilization homogeneous LDL - C assay ( SOL) from KyowaMedex , Surfactant LDL - C assay ( SUR) from Daiichi Pure Chemicals , Protecting LDL -assay reagent ( PRO) from Wako Chemicals , LDL - C assaycatalase ( CAT) Denka Seiken and Calixarene of LDL - C assay ( CAL) from International Reagents Corporation . A ll method is to use a variety of detergents and other chemicals that cause blocking or dissolution of specific lipoprotein classes to achieve specificity for LDL . Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: homogenous assay, LDL, lipoprotein